Supportiveness of language MOOCs for self-regulated learning: a review of commercial language MOOCs on the market. (9th June 2022) - Zhang, Ruofei; Zou, Di; Cheng, Gary; Xie, Haoran; Wang, Fu Lee
MOOCs have been frequently applied as an effective approach to language education, especially when they can support self-regulated learning. However, few studies have discussed the supportiveness of using MOOCs for language education (i.e. language MOOCs) on the market for self-regulated learning. This study therefore presents a review of 78 commercial language MOOCs on the market, focusing on the supportive MOOC features for self-regulated learning. From this review, we identify that language MOOCs can support self-regulated learning by pre- and post-course surveys, frequently asked questions, information about instructors, follow-up questions, previews, summaries, discussion forums, social networking, learning progress bars, system-generated emails, multimedia supplementary learning materials, instructional games, wiki-based collaborative writing activities, as well as quizzes and final exams graded by peers and instructors. This study also discusses the implications of the results for the practitioners, designers and researchers of language MOOCs.